The Modulation and Coding Scheme for the Command and Telemetry Radio Line of Communications with Re-Entry Spacecraft - Tereshonok, M. V.; Klenov, N. V.; Lobov, E. M.; Shubin, D. N.; Kandaurov, N. A.; Lipatkin, V. I. (Journal of communications technology & electronics, 2022)
The modulation and coding scheme for a modem is proposed, taking into account the features of a promising method of overcoming plasma radio blackout during re-entry of a spacecraft. The communications range is estimated taking into account losses in the atmosphere and in the plasma layer when using a resonator matched to plasma parameters.